2022
DOI: 10.1186/s13021-022-00219-5
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil respiration to changes in soil temperature and water table level in drained and restored peatlands of the southeastern United States

Abstract: Background Extensive drainage of peatlands in the southeastern United States coastal plain for the purposes of agriculture and timber harvesting has led to large releases of soil carbon as carbon dioxide (CO2) due to enhanced peat decomposition. Growth in mechanisms that provide financial incentives for reducing emissions from land use and land-use change could increase funding for hydrological restoration that reduces peat CO2 emissions from these ecosystems. Measuring soil respiration and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Carlson et al (2015) indicated that peat depth and time since draining are not significant predictors, while vegetation age is a strong predictor due to the rate of root respiration [ 56 ]. Swails et al (2022) observed that soil respiration on peatland is linked to soil temperature [ 81 ]. This research also determined that water content, with an average water content during the six-month research period of 273% ± 79%, is not a significant predictor of CO 2 emission estimation (R 2 = 0.000, p value = 0.773).…”
Section: Discussionmentioning
confidence: 99%
“…Carlson et al (2015) indicated that peat depth and time since draining are not significant predictors, while vegetation age is a strong predictor due to the rate of root respiration [ 56 ]. Swails et al (2022) observed that soil respiration on peatland is linked to soil temperature [ 81 ]. This research also determined that water content, with an average water content during the six-month research period of 273% ± 79%, is not a significant predictor of CO 2 emission estimation (R 2 = 0.000, p value = 0.773).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrological alteration generated by drainage is one of the most generalized anthropogenic disturbances and the one that produces the greatest damage on a peatland because primary productivity and OM degradation are closely linked to WT position (Evans et al., 2021; Huang et al., 2021; Laiho, 2006; Loisel et al., 2021; Strack & Price, 2009). The decline in WT generally alters the dynamics and C balance of the ecosystem (Chimner et al., 2017; Goodrich et al., 2015; Minkkinen et al., 1999; Strachan et al., 2016), because increased oxygen availability in the unsaturated surface stratum (acrotelm) favors respiration and oxidation of OM, increasing CO 2 emissions (Figure 3) (Huang et al., 2021; Ma et al., 2022; Peichl et al., 2014; Strack et al., 2014; Swails et al., 2022). On the other hand, anaerobic conditions fostered by elevated WT favor the accumulation of recalcitrant compounds derived from Sphagnum by inhibiting OM degradation through a mechanism known as “enzymatic latch” (Abbott et al., 2013; Freeman et al., 2001; Kim et al., 2021).…”
Section: Direct Anthropogenic Disturbances Exerted On Sphagnum Mosses...mentioning
confidence: 99%
“…Total soil CO 2 efflux is the second largest carbon flux (after photosynthesis) in terrestrial ecosystems [ 16 ] and is a result of autotrophic (CO 2 produced by vegetation living roots) and heterotrophic (CO 2 produced by soil microbes in the decomposition of organic matter deposited into soil and on the soil surface) soil respiration [ 17 , 18 , 19 ]. The total soil respiration rate depends on many variables such as local climate, land use, nutrient availability, soil temperature, soil moisture, and water table level (WTL) [ 20 , 21 , 22 , 23 ]. Generally, lower WTL in drained areas has a positive effect on oxygen availability, which can enhance oxidation and decomposition at greater peat layer depth from the soil surface [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%